JUAL BELI PADI DENGAN SISTEM HARGA URIP DALAM PERSPEKTIF EKONOMI ISLAM DI DESA TANJUNG TIGA - Nia Andria Erzah; Witry Octasari Aritonang; Srinanti (Program Studi Ekonomi Syariah, 2025)
The life-price system (harga urip) refers to a pricing mechanism in which the price is not determined at the time of contract but is adjusted later based on the highest market price. This practice has long been accepted as a local custom (???urf). This study aims to analyze the practice of rice trading using the harga urip pricing system implemented by the community of Tanjung Tiga Village, Rantau Bayur District, Banyuasin Regency, and to examine its conformity with Islamic economic principles, particularly regarding contractual clarity and transactional justice. The research employs a qualitative method with a case study approach. Data were collected through field observations, semi-structured interviews with rice farmers and purchasing agents, and relevant documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, supported by triangulation techniques to ensure data validity. The findings indicate that the rice trading practice under the harga urip system generally fulfills the pillars of sale (rukun al-bay???), including the presence of contracting parties, a clear object of transaction, and mutual agreement. However, in terms of the legal conditions of sale, several issues were identified, particularly the uncertainty of price and payment timing, which may lead to elements of gharar. In some cases, such uncertainty resulted in actual losses for farmers, while in other cases the system functioned fairly due to strong trust and moral commitment between parties. Therefore, the harga urip system cannot be categorically deemed unlawful, but it requires clearer contractual arrangements to align with the principles of justice and the objectives of Islamic law (maqashid al-shariah).